Perbandingan Motif Cerita Rakyat Asal-usul Tradisi Tiban di Karesidenan Kediri - Inayatul Luthfiyyah; Ari Widihastuti, Rahma (Sutasoma : Jurnal Sastra Jawa, 2024)
Many folklore from various regions show similarities, especially in the story's motif, as seen in the folklore of the Tiban Tradition in Kediri Residency, which is related to culture and beliefs. This research aims to identify the motifs in the folklore of the Tiban tradition in Kediri Residency, precisely in Purwokerto Village, Kediri Regency and Wajak Village, Tulungagung Regency. This study uses qualitative methods and Stith Thompson's motive theory to analyze the motives in the story. A comparative literary approach is used to compare the two stories. The data collection and data analysis methods used an ethnographic approach. By comparing motifs in Tiban traditional folklore in Purwokerto Village and Wajak Village, this study found 23 data and 11 types of motifs. The results of the study found that there are six-story motifs in Purwokerto Village, namely marvels motifs, magic motifs, traits of character motifs, mythological motifs, sacrifices motifs, and symbolic motifs. In Wajak Village, there are five motifs, namely the test motif, the sacrifice motif, the traits of character, the symbolic symbolism, and the marvels motif. Therefore, four similar motifs and three different motifs were found.